2019
DOI: 10.3139/146.111698
|View full text |Cite
|
Sign up to set email alerts
|

Effect of powder morphology on the microstructure and properties of cold sprayed Ni coatings

Abstract: Cold sprayed Ni coatings offer new possibilities for repairing damaged and mis-machined components. The morphology of the powder particles and grain-size distribution have a significant influence on the particles' behaviour during compaction and on the properties of the coating. In this study, two Ni powders with different morphology and grain-size distribution were cold sprayed on a 7075 Al alloy substrate. The first powder, Ni HR, had an irregular spherical shape, whereas the second, Ni E, possessed a dendri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Therefore, the main advantage of cold-sprayed coatings is the lack of defects typical of thermally sprayed coatings, such as oxidation, evaporation, gas release, and shrinkage porosity. The absence of oxides in cold-sprayed titanium coatings has also been reported by other researchers in the case of powders with angular morphology but different particle size distribution applied as the feedstock material [ 54 , 56 , 66 , 67 , 68 , 69 ]. However, some reports show a negligible increase in the contents of oxygen and nitrogen in the cold-sprayed coatings in comparison with the starting feedstock [ 52 , 57 ].…”
Section: Resultssupporting
confidence: 72%
“…Therefore, the main advantage of cold-sprayed coatings is the lack of defects typical of thermally sprayed coatings, such as oxidation, evaporation, gas release, and shrinkage porosity. The absence of oxides in cold-sprayed titanium coatings has also been reported by other researchers in the case of powders with angular morphology but different particle size distribution applied as the feedstock material [ 54 , 56 , 66 , 67 , 68 , 69 ]. However, some reports show a negligible increase in the contents of oxygen and nitrogen in the cold-sprayed coatings in comparison with the starting feedstock [ 52 , 57 ].…”
Section: Resultssupporting
confidence: 72%
“…The very high roughness of Ni coatings (Table 3) with visible craters confirmed this assumption. On the other hand, the application of finer powders allowed the microstructure to be improved [38,39]. Moreover, quiet crackling was heard during indentation, which confirmed very high stress inside the coatings caused by particles impacting the previously deposited layer with very high velocity.…”
Section: Mechanical Characteristicsmentioning
confidence: 85%
“…Adiabatic shear instability takes place when the critical velocity of particles is exceeded, which causes the occurrence of shearing at high pressure, followed by an increase in temperature at the high strain rate of the deformation. The heat generation and high deformation of the powder were mainly localized near the interface region causing the generation of shear bands by adiabatic shear localization [27]. An adiabatic softening of particles favors the good connection of their surfaces by plastic deformation.…”
Section: Residual Stressmentioning
confidence: 99%
“…Ajdelsztajn et al [26] reported that Ni powders of irregular shape are more suitable to obtain a dense coating than spherical ones, because they acquire much higher impact velocity. Góral et al [27] showed that it is possible to produce dense coatings using both dendritic and irregular spherical Ni powders. However, the coating sprayed with dendritic powder exhibited better mechanical properties and significantly lower surface roughness in comparison with the deposit sprayed with spheroidal particles.…”
Section: Introductionmentioning
confidence: 99%